LICENSING ACCOUNTING EVALUATION ONLINE SINGLE SUBMISSION: (Study On DPMPTSP Kabupaten Blitar) - Dita Nurul S (Universitas Islam Balitar, 2020)
Information and communication technology that is growing rapidly now influences the bureaucracy to utilize information technology as a means of improving the implementation of business acceleration. Through this online integrated Online Single Submission (OSS) licensing service, it is able to shorten the service time and making business licenses applied by Blitar DPMPTSP according to the mandate of Government Regulation Number 24 of 2018.The purpose of this study is to evaluate the Online Single Submission (OSS) licensing accounting system at DPMPTSP Blitar Regency. The research method used by researchers is qualitative descriptive with resource persons licensing officials. The results of the study confirm that there are still obstacles regarding the lack of public understanding of business licensing through Online Single Submission (OSS) so that there is a need for socialization and overall assistance to the community and related institutions.